Method of wireless transmission of digital information on the basis of ultra-widesignals - Serkov, Aleksandr; Trubchaninova, Karina; Mezitis, Mareks (Національний технічний університет "Харківський політехнічний інститут", 2019)
The subject of the study are the organization of wireless transmission of digital information based on ultra-wideband signals. The goalis the development of models and methods for organizing broadband wireless communications operating in difficult interference environments. The taskis to ensure the stable and safe operation of communication systems. The methodology is based on the method of generating ultra-wideband digital signals and the method of extracting ultra-wideband information signals in the communication channel with interference. The methods used: methods of analytical, simulation and inverse Fourier transform. The following results are obtained. A technique has been developed for wireless transmission of digital information based on ultra-wideband signals, which includes a method for generating ultra-wideband information signals with code spectral modulation and a method for extracting information signals in a communication channel with interference. An assessment of the effect of interference onthe quality of the information being restored is performed. A special class of intra-system interference has been identified, which appears due to the multiplicity of delays in the information bit stream T0or T1. It is shown that their appearance leads to an increase in the bit error when extracting information signals in the communication channel. A mechanism is proposed foreliminating these errors by setting the multiple delays T0 and T1 when generating ultra-wideband information signals. Conclusions. The use of communication channels with an ultra-wide frequency band makes it possible to simultaneously implement a set of requirements for the electromagnetic compatibility of telecommunication systems, high-speed transmission of information with high noise immunity with respect to external interference.

Предметом вивчення є організація безпроводової передачі цифрової інформації на грунті надширокосмугових сигналів. Мета – розробка моделей і методів організації надширокосмугового беспроводового зв’язку, що працює в умовах складної завадової обстановки. В основу методики покладено метод формування надширокосмугових цифрових сигналів та метод вилучення надширокосмугових інформаційних сигналів в каналі зв’язку з завадами. Задача – забезпечення усталеної та безпечної роботи системи зв’язку. Використані методи: методи аналітичного, імітаційного моделювання та зворотнього перетворення Фур’є. Отриманінаступні результати. Розроблена методика безпроводової передачі цифрової інформації на грунті надширокосмугових сигналів, до складу якого включено метод формування надширокосмугових інформаційних сигналів з кодовою спектральною модуляцією та метод вилучення інформаційних сигналів в каналі з завадами. Виконана оцінка впливу завад на якість передаваємої інформації. Виявлено особливий клас внутрiшньосистемних завад, які з’являються внаслідок кратності затримок в інформаційному потоці бітів T0 або T1. Показано, що їх поява призводить до підвищення бітової похибки під час вилучення інформаційних сигналів в каналі зв’язку. Запропоновано механізм усунення цих похибок шляхом встановлення некратних затримок T0 і T1 під час формування надширокосмугових інформаційних сигналів. Висновки. Використання каналів зв’язку із надширокою смугою частот дає можливість одночасної реалізації комплексу вимог по електромагнітній сумісності телекомунікаційних систем, великій швидкості передачі інформації з високою завадостійкістю по відношенню до дії зовнішніх завад.
Методика безпроводової передачі цифрової інформації на грунті надширокосмугових сигналів
Keywords: correlation technique; coherence; кореляційний прийом; когерентність